Investigation of surface film formation on LiNi0.5Mn1.5O4 cathodes in carbonate based liquid electrolytes using the secondary ion mass spectrometry - Falk, Mareike; Justus Liebig University Giessen (My University, 2014)
The scope of the present work was the investigation of the interface film formed between LiNi0.5Mn1.5O4, a cathode material for lithium ion batteries, and liquid carbonate based electrolytes. Main characterization tool was the secondary ion mass spectrometry. Thin film model electrodes, which are in contrast to technical electrodes free of conductive carbon and binder, were studied in order to exclude the influence of these additives on the surface film formation and to simplify the system. By usage of thin film electrodes in addition the electrode roughness could be distinctly reduced. This in turn increases the depth resolution of the secondary ion mass spectrometry. Main aim during thin film optimization was the reduction of the electrode roughness. Mainly by increasing the deposition temperature values of less than 10 nm could be reached. It could be revealed that the interface film shows a stacked structure. The region close to the electrolyte is mainly composed of organic species, while mainly inorganic ones are located close to the cathode surface. The thickness of the interface film increases with cycle number, storage time and temperature. Both transition metals contained in the cathode show significant dissolution in the electrolyte and diffuse through the electrolyte towards the anode. A model concerning the surface film formation was developed.

Im Rahmen der vorliegenden Arbeit wurde die Grenzschicht zwischen LiNi0,5Mn1,5O4, einem Kathodenmaterial für Lithiumionenbatterien, und flüssigen, carbonat-basierten Elektrolyten untersucht. Die Hauptanalytik wurde dabei mittels Sekundärionen-Massenspektrometrie durchgeführt. Es wurden Dünnfilm-Modellelektroden, die im Gegensatz zu technischen Elektroden keine Leitfähigkeitszusätze und Binder enthalten, untersucht, um den Einfluss dieser Zusätze auf die Grenzschichtbildung auszuschließen und das System zu vereinfachen. Außerdem konnte so die Rauigkeit der Elektroden deutlich reduziert werden, wodurch sich die Tiefenauflösung der Sekundärionen-Massenspektrometrie signifikant verbesserte. Hauptziel der Dünnfilmoptimierung war somit die Reduzierung der Rauigkeit der Elektrode. Vor allem durch Erhöhung der Abscheidetemperatur wurden Werte unter 10 nm erreicht. Es konnte gezeigt werden, dass die Grenzschicht einen schichtartigen Aufbau aufweist. Vorwiegend organische Spezies befinden sich auf der Elektrolytseite der Schicht, während im Bereich nahe der Kathodenoberfläche vor allem anorganische vorliegen. Die Dicke der Schicht wächst mit Zyklenzahl, Lagerungzeit und Temperatur. Beide im Kathodenmaterial enthaltenen Übergangsmetalle zeigen zudem signifikante Löslichkeit im Elektrolyten und diffundieren durch diesen bis zur Anode. Weiterhin wurde ein Modell zur Ausbildung der Grenzschicht aufgestellt.
Aufklärung der Oberflächenfilmbildung auf LiNi0.5Mn1.5O4 Kathoden in flüssigen carbonatbasierten Elektrolyten mittels Sekundärionen-Massenspektrometrie
Keywords: Lithiumionenbatterie; LiNi0.5Mn1.5O4; Sekundärionen-Massenspektrometrie; Dünnfilmelektrode; lithium ion battery; LiNi0.5Mn1.5O4; secondary ion mass spectrometry; thin film electrode; ddc:540